The Influence Of Employer Branding On Proactive Work Behaviour Among Academicians In Private Higher Education Institutions: Work Engagement As A Mediator - Cheah, Chew Sze (2020)
The constant shift experienced in the business realm has always affected the academic domain. In order to stay competitive, being proactive is in essence. The term ‘proactive behaviour’ has garnered much attention from scholars since the past two decades due to its significantly positive effect on work. In light of the academic community, this very concept, nonetheless, has remained untapped; thus the pressing need for rigorous seminal studies to validate proactive behaviour in this academic context. In line with the strong belief in fabulous brand held by the management, universities are expected to attract not only students, but also multiple talents to enhance their performances